Effects of seeds treated with cobalt nanoparticles on germination, growth, yield and quality of soybean cultivar DT12 - Hien, Le Thi Thu; Truong, Tran Thi (Academia Journal of Biology, 2019)
Seed treatment using metallic nanoparticles to stimulate germination and improve crop yields has been published and widely applied in agriculture production. To assess the safety of such methods on plants, the effectiveness and safety of the treatment of soybean Glycine max L. DT12 seeds with cobalt nanoparticles (nCo) before sowing were investigated. Seeds of soybean cultivar DT12 were treated with nCo at two different concentrations (0.165 and 1.65 mg/kg seed) before sowing. Germination rate, growth speed, soybean yield and bean nutrient components were examined throughout a season. Results implied that at a concentration of 0.165 mg/kg, nCo significantly increased germination rates, plant heights, total pods per plant, number of pods having 3 seeds, and crop productivity compared to both the control and seeds treated with a highter concentration of 16.5 mg per kg of seed. However, no significant differences were found between treatments in terms of growth level and seed nutrient contents, including moisture, ash content, mineral (K, Mg and Fe) and crude protein components. In seeds treated with higher concentration, the Ca content was dramatically lower than that of the control and seeds treated with a low concentration, but bean quality was not affected. This study contributes to the effective and sustainable application of nanomaterials in Vietnamese agriculture.